COMPARISON OF SINGLE VERSES MULTIPLE SESSION BAND LIGATION FOR THE TREATMENT OF BLEEDING OESOPHAGEAL VARICES - Hyder, Ali; Dilshad, M Akif; Sarwar, Shahid; Alam, Altaf; Khan, Anwaar A; Butt, Arshad Kamal (Journal of Ayub Medical College Abbottabad, 2015)
Background: Cirrhosis of liver is the leading cause of portal hypertension in this part of the globe. Around thirty percent of the patient with portal hypertension develops complications. Oesophageal variceal bleeding is a serious complication of portal hypertension. Oesophageal variceal band ligation (EVBL) has become the standard of care for patients with bleeding oesophageal varices. Multiple sessions of band ligation are cumbersome and expensive. Methods: Sixty patients with acute variceal bleed were enrolled in this randomized control trial. Patients were randomly assigned to multi-session (group A) or single session (group B) oesophageal variceal band ligation group. All patients were followed for re-bleeding and mortality up to three months. Results: Re-bleeding occurred (20%) in group A and (17%) in group B patients, respectively. Mortality was 10% in group A and 7% in group B patients. Variceal obliteration was better in group A 63% than group B 24% (p<0.05). Conclusion: Single session band ligation was comparable for rates of re-bleeding and mortality to multi-session band ligation. Keywords: Cirrhosis of Liver, Oesophageal Varices, Band Ligation